2003
DOI: 10.1080/10446670310001626553
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Anti‐Phospholipid Antibodies (APLA) and Attention Deficit/Hyperactivity Disorder (ADHD) in Children

Abstract: Numerous studies have shown the pathological influence anti-phospholipid antibodies (APLA) have on the physiology of the single neuron as well as the function of the entire human nervous system. The influence is well demonstrated in the antiphospholipid syndrome (APS). This syndrome is characterized by a triad of arterial or venous thrombotic events, recurrent fetal loss and thrombocytopenic purpura. The syndrome exhibits different neurological pathologies such as: chorea, seizures, transverse myelopathy, migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Children were described by the mothers during the interviews as having a generally good psychological outcome without a shared personality trait; however, 2 of 15 children were described as hyperactive. According to the literature, the occurrence of attention deficit/hyperactivity disorder (ADHD) in mice is supposedly induced by the presence of aPL; on the contrary, in a study of 41 children affected by ADHD, no evidence of a relationship between this condition and aPL was reported (31).…”
Section: Discussionmentioning
confidence: 99%
“…Children were described by the mothers during the interviews as having a generally good psychological outcome without a shared personality trait; however, 2 of 15 children were described as hyperactive. According to the literature, the occurrence of attention deficit/hyperactivity disorder (ADHD) in mice is supposedly induced by the presence of aPL; on the contrary, in a study of 41 children affected by ADHD, no evidence of a relationship between this condition and aPL was reported (31).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on mice induced with antiphospholipid (APL) syndrome using monoclonal anticardiolipin antibodies, Ziporen, Shoenfeld, Levy, and Korczyn (1997) reported that the mice exhibited hyperactive behavior compared with the control group. The results of a human study by Bujanover et al (2003) did not support this association and suggested no significant difference in the level of APL antibody measured between the ADHD children and the controls. Although there was some evidence supporting the possible role of autoimmunity in ADHD, the results were still controversial.…”
Section: Adhd and Autoimmune Diseasesmentioning
confidence: 92%